Primernaija klassifikacija bazovych dvigatel'nych koordinacij po rjadu obscich i specificeskich priznakov i strukturnych elementov - Nazarenko, L. D. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The control of movements is the complex on it's structure processes, provided with functions of the various systems of a body. The approximate classification of the base motor coordinations offered by the author is developed on the basis of the number of the common and specific attributes of structural elements in a different degree inherent to each of them. Such basic components as synchronization of motor and vegetative functions, redistribution of muscular efforts in space and time, the degree of the interaction of sensory systems, the level of intermuscular and intramuscular coordination are typical for the all investigated base motor coordinations. The classification offered by the author allows to propose the available representations and the data of the research of the base motor coordinations and to consider them as the uniform complex of the qualitative sides of the motor activity in the aggregate with the physical capasities (muscular power, speed, endurance).